Effective negotiating : teacher's book - Comfort, Jeremy (Oxford : Oxford University Press, 1996)
This book is divided into eight units: Preparing the ground, Setting the Agenda, Establishing positionss, Clarifuing positions, Managing conflict, Making and responding to proposals, Bargaining, and Concluision and agreement.
Keywords: English language; Business; Negotiation; Negotiation in business; English language -- Business English